Subclinical Hypothyroidism and Depression: A Systematic Review and Meta-Analysis - Tang, Rong; Wang, Jian; Yang, Lili; Ding, Xiaohong; Zhong, Yufan; Pan, Jiexue; Yang, Haiyan; Mu, Liangshan; Chen, Xia; Chen, Zimiao (Frontiers in Endocrinology, 2019)
Abstract Background: Thyroid function is closely associated with neuropsychological functions, including mood and cognitive functions. Although thyroid function is routinely examined in patients with depressive symptom, the association between subclinical hypothyroidism (SCH) and depression remains inconclusive. Objective: This systematic review and meta-analysis aimed to evaluate the risk of depression in patients with SCH. Methods: The PubMed, Embase, and Web of Science databases were searched up to August 2018. The primary outcome was the prevalence of depression, as evaluated by various types of self-reported depression scales. Odds ratios (ORs) were calculated to compare the risk of depression between patients with SCH and those with euthyroid. Results: Twenty-one studies were included in the systematic review, with a total of 103,375 subjects from 7 studies being pooled for the meta-analysis to evaluate the risk of depression. The meta-analysis showed patients with SCH had a significantly elevated risk of depression than patients with euthyroid (OR = 1.78, 95% confidence interval [CI]: 1.11–2.86, P=0.02). No publication bias was found, as indicated by Egger’s test (t=-0.49, P=0.647) and Begg’s test (z=-0.15, P=0.881). In addition, the funnel plot showed a symmetric distribution. Conclusions: This meta-analysis demonstrated that SCH was positively associated with the risk of depression, suggesting it is necessary to pay close attention to depressive symptoms in patients with SCH.